Internet of Things: Web-Based Questionnaire for University Evaluation - Fahad Layth Malallah; Mustafa Ghanem Saied; Maher Talal Alasaady; Baraa T. Shareef (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Recently, questionnaire-based web-pages are getting popular around the world due to its simplicity in terms of management by databases as well as collecting more opinions than the paper-pages base. The motivation is to measure the degree of students’ satisfaction with a number of educational, social, and environmental aspects of the university, with targeting to assess quality, performance, productivity, and innovation then send the information to the university management by Internet. In this paper, students’ satisfaction questionnaire based on web-pages is elaborated in terms of design and implementation. This questionnaire detail has been collected officially from the department of quality assurance of Ninevah University as a case study. As an implementation, Spiral model with an iterative flow is selected as the methodology by using web programming tools to construct the online form pages, which are HTML, CSS, JavaScript, and PHP. In other words, this research proves that university evaluation cycles can be completely done by using the Internet to be one of the applications of Internet of Things (IoT), which is considered as the contribution of this paper. In which it is done by setting up a client-server network connection as TCP/IP protocol. The result shows a promising mechanism to provide the university with useful statistical information effortlessly and accurately.